Comparative examination of levodopa pharmacokinetics during simultaneous administration with lactoferrin in healthy subjects and the relationship between lipids and COMT inhibitory activity in vitro. (4th March 2022) - Nagai, Masahiro; Kubo, Madoka; Ando, Rina; Ikeda, Masayuki; Iwamoto, Hiroshi; Takeda, Yasuhiro; Nomoto, Masahiro
ABSTRACT: Background: Lactoferrin (bLF) is an iron-binding multifunctional protein that is abundant in milk. In mice, it inhibits catechol- O -methyltransferase (COMT) activity and increases blood levodopa levels. However, the clinical effects are unknown. Objective: The objective of this study was to determine the effect of bLF on the kinetics of levodopa in blood. Design: The effects of the concomitant administration of a combined formulation of levodopa and an aromatic amino acid decarboxylase inhibitor and bLF on the concentration of levodopa in blood and its metabolism were assessed in eight healthy subjects. In addition, we analyzed the association with clinical factors and evaluated whether clinical factors affected the COMT inhibitory activity of bLF in vitro . Results: Although not statistically significant, the peak plasma concentration ( C max ) of levodopa increased by 18.5%. From the results of the stratified analysis of total cholesterol, a relationship with Δ C max was predicted. Therefore, bLF was reacted with cholesterol in the presence of lecithin and sodium deoxycholate in vitro to evaluate COMT inhibitory activity, and an increase in inhibitory activity was observed. By contrast, the ester compound cholesteryl oleate had no effect. The inhibitory activity of free fatty acids, which are known to interact with bLF, was also enhanced. Conclusion: The COMT inhibitory activity of bLF is not effective in elevating blood levodopa levels. However, in humans with high lipid levels, such as cholesterol, interactions may enhance the inhibitory effect, resulting in the enhanced absorption of levodopa. Trial registration: ID, UMIN000026787, registered 30 March 2017; URL, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000030749 Trial registration: UMIN Japan identifier: UMIN000026787